Prosthodontics Using Removable Platform Switching Technologies (Multiunit, On1) as Exemplified by Conical Connection Implant Systems for Early and Immediate Loading - Roman Studenikin (International Journal of Dentistry)
The removable platform switching technology (multiunit, Оn1) was tested intraoperatively using the passive placement technique as exemplified by a conical connection implant system, which makes it possible to visually control the placement of these platforms with respect to the alveolar bone in the correct orthopedic position. The technology is characterized by a rapid epithelialization of tissues around the base platform until the final integration of the implant, minimal trauma in the emergence profile zone, and an improved minimally invasive orthopedic protocol for working on a removable platform switching base.